2013
DOI: 10.1371/journal.pone.0057535
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Bifidobacterium longum subsp. infantis Reveals the Metabolic Insight on Consumption of Prebiotics and Host Glycans

Abstract: Bifidobacterium longum subsp. infantis is a common member of the intestinal microbiota in breast-fed infants and capable of metabolizing human milk oligosaccharides (HMO). To investigate the bacterial response to different prebiotics, we analyzed both cell wall associated and whole cell proteins in B. infantis. Proteins were identified by LC-MS/MS followed by comparative proteomics to deduce the protein localization within the cell. Enzymes involved in the metabolism of lactose, glucose, galactooligosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…Additionally, strain does not show any preference for glucose and this parallel with a previous study concerning its behaviour relation to galactose, glucose and lactose uptake on the mixture of monosaccharides [18]. …”
Section: Changes Of Carbohydrates In Skim Milk During B Pseudocatenusupporting
confidence: 89%
“…Additionally, strain does not show any preference for glucose and this parallel with a previous study concerning its behaviour relation to galactose, glucose and lactose uptake on the mixture of monosaccharides [18]. …”
Section: Changes Of Carbohydrates In Skim Milk During B Pseudocatenusupporting
confidence: 89%
“…This compound is abundant in plasma but not observed in either bovine or human milk. We have previously shown that there are glycosidases produced by commensal bacteria in the infant gut [30], therefore we may speculate that U-SLN and other sialylated compounds can be produced by the interaction of milk, milk products and bacterial enzymes, i.e. an in vivo example of a new oligosaccharide structure produced by the gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…First, transporter proteins that bind to specific HMO linkages, including a number of solute-binding proteins with an affinity for HMOs, are upregulated in B. infantis grown on HMO but not in B. infantis grown on the simpler prebiotic oligosaccharides fructo-oligosaccharide or galacto-oligosaccharide (29,30). This suggests that B. infantis is able to transport intact HMOs into its cytoplasm and that this capacity is “turned on” by the HMOs.…”
Section: Mechanistic Evidence For Colonization By B Infantismentioning
confidence: 99%